Combined impact of pesticides on mono- and bilayer lipid membranes - Morato, Luis Fernando do Carmo [UNESP]; Ruiz, Gilia Cristine Marques [UNESP]; Lessa, Carlos Junior Amorim [UNESP]; Olivier, Danilo da Silva; Amaral, Marcos Serrou do; Gomes, Orisson Ponce [UNESP]; Pazin, Wallance Moreira [UNESP]; Batagin-Neto, Augusto [UNESP]; Oliveira, Osvaldo N.; Constantino, Carlos José Leopoldo [UNESP] (Elsevier, 2025)
The increased use of agrochemicals in crop production raises concerns about the risk of combined pesticide exposure through water and food, potentially leading to a ‘cocktail effect’ with synergistic impacts on human health. To investigate such effects, we used the pesticides acephate and diuron interacting with a mimetic system of the cell membrane, composed of lipid monolayers. These mimetic systems were composed by a mixture of POPC, cholesterol and sphingomyelin (70/20/10 mol%), respectively, close to the composition found in mammalian membranes. Results from Langmuir monolayers, including surface pressure-area isotherms, polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS), and Brewster angle microscopy (BAM), showed that the pesticides interact predominantly with the polar head region of the lipids, a finding supported by density functional theory (DFT) calculations and molecular dynamics simulations. The cocktail had a similar effect in π-A isotherms; however, PM-IRRAS data suggests a stronger effect of the cocktail on the ternary monolayer at the molecular level, once the pesticide mixture changed the conformation and orientation of the headgroup and disturbed the hydrocarbon chain. These results evidence the impact of the ‘cocktail effect’ on lipid membranes, highlighting potential health risks associated with pesticide mixtures.
Keywords: 2D assembly; Bilayer; Biointerfaces; Langmuir film; Pesticides; Theoretical-experimental analyses